Nilai Pendidikan Karakter Dalam Cerita Rakyat Jambi dan Relevansinya dengan Pembelajaran Bahasa Indonesia di SMP - Wahyuningsih, Isti; Akhyaruddin, Akhyaruddin; Setyonegoro, Agus; Dewi, Yusra; Purba, Andiopenta (Universitas Batanghari Jambi, 2023)
The purpose of this study was to describe the value of character education contained in Jambi folklore and its relevance to learning Indonesian in junior high schools. This research is in the form of qualitative descriptive. The data of this study is the value of character education in twelve Jambi folk tales and the data source is the bilingual Jambi Folklore book with twelve story titles, namely 1) Black Water and Clear Water, 2) Swearing Stone, 3) Buffalo Stone, 4) Likat Lake, 5) Datuk Blood Putih, 6) Datuk Kerungkung Bebulu, 7) Dideng Dang Ayu, 8) Girls with Long Hair, 9) Lubuk Bujang Girls, 10) Smooth People, 11) Rice as Big as a Coconut, 12) Tama Tujeuh. The findings from this study include: there are five aspects of character education proclaimed by the Ministry of Education and Culture, namely religious, nationalist, independent, mutual cooperation and integrity and Jambi folklore is relevant to learning Indonesian in junior high school because it can be used as teaching material.Â